Cognitive function, emotion regulation and social-support in self-care among individuals with hypertension - Arora, Akanksha; Puar, Sonia; Srivastav, Deepika; Kumar Agarwal, Santosh (International Journal Of Community Medicine And Public Health, 2025)
Background: Hypertension, a crucial chronic disease risk factor in India, has been highlighted in recent epidemiological studies to be surging in rural and young populations. The incidence of adverse events by cause of hypertension related cardiovascular health illness is on peak. Hypertension is recognized as the most consistent risk factor for cognitive decline, associated with reduced executive functioning, slowed processing speed and deficits in memory. Additionally, the socio emotional factors like emotion regulation and social support play a significant role in symptom exacerbation, poor self-care and treatment outcomes. Improving upon the cognitive and socio emotional domains becomes imperative to ensure better self-management and life outcomes. Aim of the study was to explore the role of cognitive function, emotion regulation and social support in self-care among individuals with hypertension. Methods: In this cross-sectional study, 31 adults aged 30-60 years diagnosed with hypertension, were approached through purposive sampling. The individuals were assessed using psychological measures: PGI memory scale (PGI-MS), trail making test A and B (TMT), emotion regulation questionnaire (ERQ), Duke-UNC functional social support questionnaire (DUFSS), self-care inventory (SCI). Results: Participants were adults aged 30-60 years, with a higher proportion of males. Cognitive variables-particularly memory, attention, and executive functioning-were positively associated with self-care - maintenance, monitoring, and management. FSS showed strong positive relationships with cognitive functioning, emotional regulation, and all domains of self-care. In contrast, expressive suppression was negatively related to self-care maintenance. Conclusions: The study explored the role of cognitive functioning and socio-emotional factors in individuals with hypertension implying whether improving these factors can lead to better self-care and management.